#TITLE_ALTERNATIVE# - WIDODO, BUDI
The process to take a decision of the feasibility evaluation of the information system is determined based on criteria, intuition, and regulation which is used today. However, the process will take a long time due to the act of determining which manually done and the subjectivity which is often used that influence the customer satisfaction and influence the income. Fuzzy logic is used to make a qualitative decision, that is the decision that has same characteristic with linguistic (intuition, criteria, and habits) which used to make a decision. In this case, fuzzy logic is used to determine the feasibility of information system that has been developed by Divlat Telkom. The application of fuzzy logic in the evaluation process which determine the feasibility of information system gives the result which is fast, standard (same with the regulation, criteria, and intuition), objective (same with variable that determine every decision), and doesn't need any intensive supervision from the manager. The system performance depends to the complexity (criteria from the input and output variable which is used to define membership function of those variable), the number of input and output variable, the rules which is used, the using of interferencing methods, defuzzification and the hardware.